The sanctuary of Eleusis from the accounts of antiquarian travellers (from the 17th to the 19th century): a study case on uses of material culture - Perissato, Felipe (Romanitas - Revista de Estudos Grecolatinos, 2020)
Travel accounts written by antiquarists are important sources for historians and archaeologists, as they safeguard textual descriptions and pictorial records of landscapes, monuments and artefacts, in addition to describing contemporary locals and the dynamics between ancient and modern landscapes. They can also be interpreted as records of a long historical process of successive appropriations of Classical Antiquity by the modern societies. In this sense, this article aims to present the sanctuary of Demeter and Core in Eleusis in Attica (Greece) from the travelers’ accounts from the 17th to the 19th centuries. Thus, it reframes these sources in its historical context, both understanding their relevance as an important visual and textual historical source and exploring the controversial consequences of the handling of antiques by some antiquarists.